Effect of process parameters on microstructure and properties of superalloy turbine guide castings by a novel electromagnetic oscillation method - Zong-sheng Xie; Xin Hao; Guo-huai Liu; Hang Zheng; Chi Zhang; Chu-shan Yi; Zhao-dong Wang (Journal of Materials Research and Technology)
The difficulty in grain refinement during the casting of superalloy turbine guides is the primary factor of their low percent of pass. This study innovatively employs the electromagnetic oscillation (EMO) process during pouring and solidification using self-developed device to break through this problem. The effect of various process parameters on blade microstructure is also investigated. The result shows that implementing 300 A/20 Hz optimal EMO process produces uniformly fine equiaxed grains, reducing average grain sizes by 71.83% at the blade concave and 75.80% at the inlet edge. Yield and tensile strength increased by 22.34% and 27.15%, respectively, reaching a tensile strength of 1208.09 MPa. Elongation and section shrinkage also increased by 69.67% and 19.57%, respectively. The forced oscillation of melt caused by alternating magnetic field flushes and fragments dendrites, creating numerous nucleation sites, thus promoting grain refinement. The current intensity is linearly correlated with the electromagnetic force within the melt, influencing consequent oscillation effects. The optimal electromagnetic oscillation penetration depth, calculated at 42 mm, is determined by the number of oscillations and skin effect. This depth, calculated based on the inherent properties of the alloy, is instrumental in ascertaining the optimum current frequency for this model of turbine guides, applicable across different alloy compositions. The tensile deformation behavior of castings is altered by the grain refinement induced by the EMO process, enhancing tensile properties through the promotion of more homogeneous deformation and the inhibition effect of grain boundaries and one-dimensional defects on dislocations.